Рекомендаційна система платформи для самостійного видавництва художньої літератури - Онищенко, М. Г. (ХНУРЕ, 2024)
The proposed project addresses several critical issues faced by readers and writers in the realm of amateur fiction publishing. It aims to develop a recommendation system targeting readers' interests within a platform dedicated to web-based self-publishing and consumption of fiction literature. Furthermore, the project addresses the limitations and challenges inherent in traditional publishing models. By offering a platform for independent publishing, it circumvents the barriers often faced by aspiring authors in gaining recognition and access to traditional publishing channels. By organizing a hub for the distribution of amateur fiction literature tailored to an interested audience, the system seeks to enhance the accessibility and enjoyment of literary works while empowering authors in their creative endeavors.
Keywords: видавництво; художня література